2015
DOI: 10.1155/2015/295294
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Experiment Evaluations of a Displacement Differential Self-Induced Magnetorheological Damper

Abstract: This paper presents the development of a novel magnetorheological damper (MRD) which has a self-induced ability. In this study, a linear variable differential sensor (LVDS) based on the electromagnetic induction mechanism was integrated with a conventional MRD. The structure of the displacement differential self-induced magnetorheological damper (DDSMRD) was developed, and the theory of displacement differential self-induced performance was deduced. The static experiments of the DDSMRD under different displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The straight red line is the ideal case between the amplitude of self-induced voltage and damper displacement; it indicates that the experimental dots in the same damper displacement under different dc inputs were scattered close to the trend line. This means the amplitude of self-induced voltage was proportional to the damper displacement and has a good repeatability, while in our previous works [38,39], the repeatability of the selfinduced voltage under different dc inputs was not good due to a bias at the zero damper piston displacement; the bias is 0.016 V at 0.25 A and 0.047 V at 0.5 A, respectively.…”
Section: Self-induced Performance Under Different Damper Displacementsmentioning
confidence: 71%
See 2 more Smart Citations
“…The straight red line is the ideal case between the amplitude of self-induced voltage and damper displacement; it indicates that the experimental dots in the same damper displacement under different dc inputs were scattered close to the trend line. This means the amplitude of self-induced voltage was proportional to the damper displacement and has a good repeatability, while in our previous works [38,39], the repeatability of the selfinduced voltage under different dc inputs was not good due to a bias at the zero damper piston displacement; the bias is 0.016 V at 0.25 A and 0.047 V at 0.5 A, respectively.…”
Section: Self-induced Performance Under Different Damper Displacementsmentioning
confidence: 71%
“…The specifications of the proposed MR damper are given in table 1, as are the parameters from our previous work [38,39]. Here, some key parameters were optimized to obtain better damping forces and a larger self-induced voltage in our present work.…”
Section: Structural Design Of the Proposed Mr Dampermentioning
confidence: 99%
See 1 more Smart Citation
“…The study results demonstrated that data acquisition can be realized accurately using MFL inspection technology based on LabVIEW. Hu et al [Hu, Zhou, Liao et al (2015)] presented the development of a novel magnetorheological damper which has a self-induced ability. The signal acquisition card was adopted to acquire the self-induced voltage signals, the LabVIEW interface was applied to display and analyze the displacement signals.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of self-sensing refers to the capability of one mechanical system to measure and deliver dynamic information in real time using the self-contained component of the system without the requirement for extra sensors [18][19][20]. For instance, the self-sensing technology for the self-induced velocity, displacement, and forces has been developed and feasible in the magnetorheological (MR) damper [21][22][23][24][25][26]. The practical implementation of the self-sensing feature embellishing the MRE absorber, however, has been rarely investigated according to the best knowledge of the authors.…”
Section: Introductionmentioning
confidence: 99%